Implementation of Nutritional Status Information System in Improving NCC Services - Mudiono, Demiawan Rachmatta Putro; Wicaksono, Andri Permana; Muflihatin, Indah; Nurmawati, Ida; Muna, Niyalatul; Sutantio, R. Alamsyah (International Journal of Health and Information System, 2024)
Managing data in health services is of course very complicated and requires a lot of time. Information systems in health services provide efficient benefits. The service and reporting process at the NCC is considered to be still not optimal. The impact of patient visits is still minimal and does not attract the attention of consumers. The aim of this research is to create a web-based service system at NCC. The method used is the System Development Life Cycle system development. The results of the planning found that NCC provided one of the services handled by nutritionists regarding calculating children's nutritional status based on anthropometric standards. The system analysis is divided into 2, namely functional requirements and non-functional requirements. In system design, a system flowchart, context diagram and data flow diagram are obtained. At the system implementation stage, the user has tested it using a black box test with satisfactory results